ANALISIS JARAK RUJI PADA MESIN PENGUPAS POLONG KACANG TANAH TERHADAP HASIL KUPASAN - Xander Salahudin; Sri Widodo; Muhammad Hasan Zuhdi; Danang Henri Wibowo; Rachman Satya Pamungkas; Bagas Dwi Prakoso (Wahana Ilmuwan, 2016)
Tlogopucang village is a peanut-producing village, with production reached 2,5 tons per year. However, people still use manual way to peel peanuts, with a capacity of 7 kg/hr. The capacity is low, so they need application of technology in order to increase the production capacity of peanut peeling. The purpose of this study is to determine the production capacity by varying trellis peanut peeler.This study was to design the peanut peeling machine using a ¼ hp electric motor. The machine will use the gearbox as a power transmission unit, and using a trellis paring to put pressure on the peanuts, so the peanut seeds can be separated from the pods. Trellis peeler in this study varied with a distance of 1 cm; 1,25 cm and 1,5 cm.The results obtained an average production capacity of peanut peeling machine with trellis distance of 1 cm; 1,25 cm and 1,5 cm are 43,49 kg/hr; 42,56 kg/hr and 37,73 kg/hr.